Use of a cocktail probe to assess potential drug interactions with cytochrome P450 after administration of belatacept, a costimulatory immunomodulator. (2nd November 2016) - Williams, Daphne; Tao, Xiaolu; Zhu, Lili; Stonier, Michele; Lutz, Justin D.; Masson, Eric; Zhang, Sean; Ganguly, Bishu; Tzogas, Zoe; Lubin, Susan; Murthy, Bindu
Abstract : Aim: This open‐label study investigated the effect of belatacept on cytokine levels and on the pharmacokinetics of caffeine, losartan, omeprazole, dextromethorphan and midazolam, as CYP probe substrates after oral administration of the Inje cocktail in healthy volunteers. Methods: Twenty‐two evaluable subjects received the Inje cocktail on Days 1, 4, 7 and 11 and belatacept infusion on Day 4. Results: Since belatacept caused no major alterations to cytokine levels, there were no major effects on CYP‐substrate pharmacokinetics, except for a slight (16–30%) increase in omeprazole exposure, which was probably due to omeprazole‐mediated, time‐dependent CYP inhibition. Belatacept did not cause major alterations in the pharmacokinetics, as measured by the geometric mean ratios and associated 90% confidence interval for area under the plasma concentration ‐time curve from time zero to infinity on Day 7 comparing administration with and without belatacept for caffeine (1.002 [0.914, 1.098]), dextromethorphan (1.031 [0.885, 1.200]), losartan (1.016 [0.938, 1.101)], midazolam (0.968 [0.892, 1.049]) or their respective metabolites. Conclusions: Therefore, no dose adjustments of CYP substrates are indicated with belatacept coadministration.